The Forest as Factory: Technological Change and Worker Control in the West Coast Logging Industry, 1880-1930 - Rajala, Richard (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1993)
This essay explores the technological changes which transformed the west coast logging industry during the late 19th and early 20th centuries. Scholars and popular historians alike have depicted the introduction of steam power and overhead logging systems as responses to environmental factors. The analysis offered here, presented in the context of the labour process debate, suggests that nature structured, but did not determine technological innovation. At the beginning of the period under study, the instability of the productive setting dictated that loggers' conceptual and physical skills controlled the pace of production. The adoption of increasingly sophisticated technologies by 1930 had given logging operators unprecedented power in their relationship with both nature and workers. Some new skilled positions had been created, but the overall effect of technological change was to undermine loggers' collective control over the labour process.